목재펠릿의 이용 활성화 방안 - 석현덕 (한국농촌경제연구원, 2009)
We have focused on the wood pallet as the alternative energy source to fossil fuels which can specify the Low Carbon Green Growth Policy of Korean government in mid and long run. In Korea, the wood pallet market is still in an early stage, and has a difficulty in commercializing goods for various reasons. In the supply side, it has an urgent problem such as a rise in production costs and a limited supply of raw materials due to the shortage of production bases. In the demand side, the problems such as the not-good quality of broilers, mistrusts toward distributing a poor wood pallet, and the high sale prices are getting more serious. It is not economical to replace kerosene from the wood pallet for house use not until kerosene price rises 5%, and also, to replace tax-free-diesel from the wood pallet not until tax-free-diesel price rises 15%. However, we need to actively come up with plans which can make the wood pallet be used a lot more because it is difficult to forecast exactly how oil price will change from now. In the supply side, we need to ensure price competitiveness through various cost reduction activities to improve the supply system of the wood pallet more effectively, and advance a proficiency of technicians and the rate of machine operation. In the demand side, we need to assure the consumer of the usefulness of the wood pallet and the high efficiency of boilers, and to relieve the anxiety about the instable supply problem.